Contribution of glycerophospholipids and sphingomyelin to the circulating NEFA. (July 2016) - Maier, Felicitas; Demmelmair, Hans; Fugmann, Marina; Hellmuth, Christian; Lechner, Andreas; Koletzko, Berthold; Uhl, Olaf
Abstract: Background: Serum nonesterified fatty acids (NEFA) are known to be associated with the development of insulin resistance. Recently, differences in the NEFA profile were found in subjects with history of gestational diabetes (postGDM) and healthy controls. Little is known about the NEFA sources in the postprandial state, which prevails most of the day in humans in modern societies. In the present study, we aimed to explore the potential contributions of glycerophospholipid (GPL) and sphingomyelin (SM) fatty acids to the circulating NEFA. Methods: Serum-samples of 19 postGDM women and 20 controls were obtained in fasting state (t0) and 90 minutes (t90) after an oral glucose tolerance test. Fatty acid composition of NEFA and SM were analyzed with liquid chromatography coupled to triple quadrupole mass spectrometry and GPL by gas chromatography. Results: The ratio of individual NEFA at t90 vs. t0 (t90/0-ratio) showed no difference between the two groups but increased with chain-length (7% for C16:1, 82% for C26:3). Only NEFA 10:0 was found with lower concentration at t0 and t90 in postGDM. At t90, long-chain polyunsaturated fatty acid correlated closely between NEFA and GPL in postGDM (20:5, 22:4, 22:5 and 22:6) and controls (20:3, 20:4 and 20:5). Very long-chain fatty acid 24:0 correlated significantly between NEFA and SM in postGDM and controls. Saturated and monounsaturated fatty acids correlated less between NEFA and GPL or SM. Conclusions: The NEFA composition varied highly between fasting and fed state in both groups. GPL appeared to contribute long-chain polyunsaturated fatty acid, while SM appeared to contribute very long-chain fatty acids to the NEFA pool.